Mikhail Lifshitz’s Philosophy of Art and the Marxist Horizons for the “End of Art History” - Harutyunyan, Angela (The Nordic Journal of Aesthetics, 2025)
This article takes as its starting point a key problematic in art history—namely, the discipline’s turn away from class struggle, social contradictions, and totality as central analytical categories and methodological standpoints since the 1970s. Informed by post-structuralism, art history instead embraced the collapse of “art” into any signifying practice and of “history” into textuality. Against the background of these disciplinary shifts, which paralleled millennial “end of history” narratives, the article asks whether another, non-liberal, end of art history is possible. It poses this question as a provocation, but also as an invitation to excavate a repressed tradition within the discipline—one constituted by a missed encounter between a Hegelian-Marxian philosophy of art and art history in the Soviet context. The article focuses on Soviet philosopher Mikhail Lifshitz’s reading of Marx’s conception of uneven development in the 1930s to argue that his treatment of this concept as both a philosophical foundation for Marxist art history and a key condition of the aesthetic ideal allowed him to uphold the communist project of emancipation, both within and against Stalinism and positivism. Grounded in the historical form of the division of labor, it was the non-synchronous or uneven relation between being and consciousness, art and material conditions, as well as ideality and reality, that supported Lifshitz’s Hegelian-Marxian conception of art’s ideality as both historical and transhistorical—one entangled with the communist project of emancipation. If revisited critically, Lifshitz’s Marxian philosophy of art may point toward a materialist re-politicization of the discipline before its putative “end.”